Present state of improvement of qualification of teachers of higher education institutions in the field of intellectual property - Chernenko, Yu. (Problems of Engineer-Pedagogical Education, 2021)
The article identifies the differences between foreign and domestic teacher training systems and emphasizes the importance of knowledge in the field of intellectual property for professionals in many fields, as well as their impact on the active development of innovation and technology in the country. The draft national strategy for the development of intellectual property provides for the restoration of the system of retraining and promotion in Ukraine in the first stage. The list of legislative documents that establish updated requirements for in-service training of teachers is given. Changes on professional development of scientific and pedagogical workers according to the Resolution of the Cabinet of Ministers of 21.08.2019 № 800 "Some issues of professional development of pedagogical and scientific and pedagogical workers" are analyzed. The main methods of teaching in the field of intellectual property recommended by the World Intellectual Property Organization are presented. The analysis of offers on the market of advanced training and training of intellectual property specialists in Ukraine is carried out and the list of providers of such services is given. In order to form intellectual property competencies in freelance teachers of various specialties and their graduates, it is recommended to expand the geography and diversify the offers of specialties in the market of professional development and training of intellectual property specialists in Ukraine. Emphasis is placed on the need for additional education of research and teaching staff of higher education institutions of Ukraine through the use of mixed and dual forms, which combine full-time and distance learning and use a variety of methods and effective tools currently provided by the Internet and forms of education: seminars, trainings, master -classes. The program of advanced training of pedagogical and scientific-pedagogical worker’s institutions of higher education on formation of competences in the field of intellectual property according to the accredited educational program "Management of intellectual property" in the Ukrainian engineering and pedagogical academy (Kharkiv) is substantiated.